1996
DOI: 10.1111/j.1749-7345.1996.tb00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phosphorus Requirement of Juvenile Striped Bass Morone saxatilis1

Abstract: Three experiments were performed in singlepass, flow-through systems to determine the dietary phosphorus requirement of striped bass Morone saxatilis. In Experiment 1, three semi-purified diets were formulated to contain 0.20,0.40, or 0.60% total phosphorus (entirely from animal protein) and were fed to striped bass having an average initial weight of 321 g. After 14 wk of feeding, significant differences in bone and scale mineralization were found among treatment groups. At a level of 0.40% dietary phosphorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 24 publications
3
39
2
3
Order By: Relevance
“…reported for sunshine bass (0.41%; Brown et al, 1993) and striped bass (0.35%; Dougall et al, 1996) and lower than that reported for European whitefish (0.62%; Vielama et al, 2002), red sea bream (0.68%; Sakamoto and Yone, 1973), Japanese seabass (0.68%; Zhang et al, 2006), large yellow croaker (0.70%; Mai et al, 2006), haddock (0.72%; Roy and Lall, 2003) and gilthead sea bream (0.75%; Pimentel-Rodrigues and OlivaTeles, 2001). The difference is probably due to fish species, fish size, diet composition, phosphorus sources and culture system (Schwarz, 1995;Shearer, 1984Shearer, , 1995Shearer, , 2000El-Zibdeh et al, 1995b;Riche and Brown, 1999;Avila et al, 2000;Lall and Vielma, 2001;Satoh et al, 2002).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…reported for sunshine bass (0.41%; Brown et al, 1993) and striped bass (0.35%; Dougall et al, 1996) and lower than that reported for European whitefish (0.62%; Vielama et al, 2002), red sea bream (0.68%; Sakamoto and Yone, 1973), Japanese seabass (0.68%; Zhang et al, 2006), large yellow croaker (0.70%; Mai et al, 2006), haddock (0.72%; Roy and Lall, 2003) and gilthead sea bream (0.75%; Pimentel-Rodrigues and OlivaTeles, 2001). The difference is probably due to fish species, fish size, diet composition, phosphorus sources and culture system (Schwarz, 1995;Shearer, 1984Shearer, , 1995Shearer, , 2000El-Zibdeh et al, 1995b;Riche and Brown, 1999;Avila et al, 2000;Lall and Vielma, 2001;Satoh et al, 2002).…”
Section: Discussionmentioning
confidence: 68%
“…Due to the function of phosphorus in bone structure, the vertebrae phosphorus content is considered to be the most sensitive criterion for P utilization in terrestrial vertebrates (Nelson and Walker, 1964;Ketaren et al, 1993;Rovindran et al, 1995), freshwater fish (Ketola, 1975;Watanabe et al, 1980;Ketola and Richmond, 1994;Rodehutscord, 1996;áșąsgĂ„rd and Shearer, 1997;Baeverfjord et al, 1998;Jahan et al, 2001) and marine fish (Sakamoto and Yone, 1978;Dougall et al, 1996;Borlongan and Satoh, 2001;Mai et al, 2006;Zhang et al, 2006). Fish scales are also one of the major sites of phosphorus metabolism and deposition (Lall, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deficiĂȘncia de fĂłsforo prejudica a mineralização dos ossos (Furuya et al, 2001a), a redução na taxa de crescimento e a deposição de minerais na carcaça e nos ossos (Rodehutscord & Pfeffer, 1995;Dougall et al, 1996;Hardy & Glatin III, 2002;Lall, 2002). Peixes alimentados com dietas deficientes em fĂłsforo apresentam deformidades em diversas regiĂ”es do corpo (Cheng et al, 2005), decorrentes da baixa mineralização, que resulta em ossos porosos e aumenta os casos de deformidade (Roy & Lall, 2003;Sugiura et al, 2004).…”
Section: Introductionunclassified
“…Fish have the dietary requirement of P like other animals for growth. The requirement was reported to range from 0.3 to 0.6% for channel catfish (Wilson et al 1982), rainbow trout (Rodehutscord and Pfeffer 1995), striped bass (Brown et al 1993;Dougall et al 1996), and white fish (Vilema et al 2002). However, somewhat higher requirement value of 0.7 to 0.9% was estimated for haddock (Roy and Lall 2003), red tilapia (Phromkunthong and Udom 2008), African catfish (Nwanna et al 2009), red drum (Davis and Robinson 1987), yellow croaker (Ma et al 2006), and carp (Kim et al 1998).…”
Section: Introductionmentioning
confidence: 99%